Adaptive optics for biological imaging - Kubby, Joel A. (Taylor & Francis, 2013)
"Written by an international team of leaders in the field, this comprehensive reference presents a complete overview of the core principles, state-of-the-art methods, and emerging applications of adaptive optics in biological imaging. It emphasizes the use of adaptive optics to correct wavefront aberrations caused by light propagation in biological samples. Accessible to readers without a background in optics, the book describes the fundamentals, components, and systems used in adaptive optics. It also covers optics systems as well as newer applications in this rapidly expanding field"--